As experiências dos intelectuais no processo de escolarização primária na Parahyba (1824-1922) - Espindola , Maíra Lewtchuk (2017)
The main argument of this thesis started from the supposition that during the long nineteenth century some intellectuals take part in the schooling process in Brazil, in addition to acting in schools as teachers and owning several writings aimed at education. Its major aim is to perform a reading about the experiences of these individuals in the process of primary schooling in the Empire and in the First Republic in Parahyba. Therefore, some individuals were selected - ffirst letters teachers – to understand their experiences about the educational process; apprehend the changes proposed in the long nineteenth century schooling process; understand the discourses on education carried out by these subjects and disseminated in various media such as newspapers, books, letters, reports, etc.; range and analyze some questions contained in the speeches of the selected subjects. The historical cut is from 1824 to 1922. Prosopography guides the analysis of the sources and based on it were chosen ten persons that make up this thesis, namely: Borges da Fonseca; Joaquim da Silva; Francisco Xavier Júnior; Francisca Moura; Francisco Coutinho de Lima e Moura; Coriolano de Medeiros; Catharina Moura; Olivina Olívia Carneiro da Cunha; José Gomes Coelho and Eudesia Vieira. The sources used are: printed matter; (self)biographies and biographical entries; books designed for schools; educational legislation; messages from the presidents of the province/state; public education reports; letters, crafts, circulars, offices. Based on the interpretations it was identified a long nineteenth century for the process of schooling in Parahyba, in which there were several discussions about: teaching methods, the education of women or the absence of such education, pedagogical materials, the slavery abolishment, the founding of societies and institutes. Through the analysis it was identified how these matter were posed and developed by these individuals in the state. There are six features derived from the intellectual experience of these subjects: dealt with relevant issues in the period they lived both in relation to instruction and the abolition of slavery, the writing of a national history, the reformulation of educational processes; used their conditions - be they teachers, women or blacks - to found their speech and act in society; they employed writing and the press to spread their ideals, whether they were for education, such as producing books for schools, or for other social issues; grouped around associations and institutions, which became communities of experience and shared common ideals and goals; they had connections with each other, even when they were participants of different generations, they formed networks of sociability, which guided the younger members how to proceed in society; believed that their speeches possessed educating and civilizing ties for the construction of the Brazilian nation. Finally, discussions about the period reveal a movement of ideas that passed through several proponents and public education was perceived as an important instrument of civilization of the people.